MANAJEMEN PELATIH EKSTRAKULIKULER DI RA MA’ARIF LANGUT KABUPATEN INDRAMAYU - Sehan Rifky (LPPM Universitas Muhammadiyah Cirebon, 2023)
Extracurricular Trainer Management is an important approach in managing and optimizing extracurricular activities in schools. Extracurriculars provide opportunities for early children to develop skills, interests and talents. The purpose of this research is to identify best practices that can be applied by extracurricular trainers in facilitating and advancing student development through extracurricular activities. This study used a qualitative approach with interviews and observation as a data collection method. The results of the study show that extracurricular trainers play a key role in creating an environment that supports, motivates, and facilitates students' active participation in extracurricular activities. Experienced and dedicated coaches can create a positive climate, which has a positive impact on students' academic achievement and personal development. Resource management is also an important aspect of extracurricular trainer management. In this case, coaches need to efficiently manage budgets, facilities and equipment to ensure the smooth running of extracurricular activities. In addition, trainers must also have the ability to plan and develop effective training programs, so that students can develop their skills optimally.This research also highlights the importance of good cooperation between coaches, students, schools and parents. Open communication and effective coordination can strengthen these relationships, thus providing ongoing support for extracurricular activities.